2023
DOI: 10.1002/lio2.1099
|View full text |Cite
|
Sign up to set email alerts
|

Regional distribution in female representation in US otolaryngology faculty

Abstract: ObjectivesTo quantify the current proportion of women in otolaryngology at different levels of professorship and determine whether these proportions differ by US region.MethodsAcademic rank and gender at all ACGME‐accredited otolaryngology programs in the United States were determined from departmental websites, Doximity, and LinkedIn from November 2021 to March 2022. Individuals were then further organized using US Census Bureau‐designated regions.ResultsAmong the 2682 faculty positions at 124 ACGME‐accredite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Although female representation in leadership roles has greatly improved in HICs over the years [22,26], women remain under-represented especially in senior positions. Within LMICs, female representation is reported to be much lower than that in HICs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although female representation in leadership roles has greatly improved in HICs over the years [22,26], women remain under-represented especially in senior positions. Within LMICs, female representation is reported to be much lower than that in HICs.…”
Section: Discussionmentioning
confidence: 99%
“…In a study examining the rates of change of female faculty ranks over a period of 10 years from 2012 to 2021, females were more concentrated in junior faculty ranks such as instructors, assistant professors, and lower-level associate professors than their male counterparts [19 ▪ ]. Similarly, Wand et al [22] also reported that in the United States, there has been a significant increase in female representation in junior academic positions, but very little representation in senior positions. This under representation in academic ranking is even further accentuated in Africa, and sub-Saharan Africa, where only a minority of senior academic ranks are filled by female OHN surgeons.…”
Section: Recent Findingsmentioning
confidence: 91%